Centromedial amygdala is more relevant for phobic confrontation relative to the bed nucleus of stria terminalis in patients with spider phobia. (November 2021) - Siminski, N.; Borgmann, L.; Becker, M.P.I.; Hofmann, D.; Gathmann, B.; Leehr, E.J.; Böhnlein, J.; Seeger, F.R.; Schwarzmeier, H.; Roesmann, K.; Junghöfer, M.; Dannlowski, U.; et al.
Abstract: Recent studies indicate differential involvement of the centromedial amygdala (CM) and the bed nucleus of the stria terminalis (BNST) during processing (anticipation and confrontation) of threat stimuli. Here, temporal predictability was shown to be a relevant factor. In this study, we want to investigate the relevance of these effects, which were found in healthy subjects, for anxiety disorders. Therefore, we investigated the differential involvement of CM and BNST in the anticipation and confrontation of phobic stimuli under variation of temporal predictability in spider phobia. 21 patients with spider phobia and 21 healthy controls underwent a temporally predictable/unpredictable phobic and neutral anticipation and confrontation paradigm using functional magnetic resonance imaging (fMRI) and ROI analyses. During the anticipation phase, healthy controls showed higher CM and BNST activity during the predictable compared with the unpredictable condition compared with the anxiety patients. During a confrontation phase that followed the anticipation phase, CM was more activated than BNST during the phobic compared with the neutral confrontation. While this effect was independent of threat predictability in patients, healthy controls showed higher activation in the CM compared with the BNST only during the predictable spider confrontation compared with the predictable bird confrontation. The results contribute to a better understanding of the separate roles of the CM and BNST during phobic processes. The CM was found to be more relevant to phobic confrontation in patients with spider phobia compared with the BNST.